Mengukir Prestasi dan meraih ridho Ilahi - Buru, Asmad Jakia (Maliki Interdisciplinary Journal, 2025)
Self-knowledge is a process that must be carried out by every individual. In this process, a person most likely knows his strengths and weaknesses. Strength does not always bring benefits, on the other hand, weakness does not always cause misplacement. However, if both are managed well it will create something extraordinary. That Students must know their own knowledge to get the best performance. Some things that need to be considered are: learning style, emotions and way of life orientation, learning style tends to be auditory. They manage their emotions quite well, and their way of life is focused on three things, namely: passion, family harmony, and achievement. Based on the results of this social service, students and teachers must utilize and maximize them well so that their positive potential can be optimized and developed well both individually and collectively in educational institutions.